Egy magyaros delikátesz-bisztró beruházás-gazdaságosági vizsgálata és üzleti terve - Kalcsics Lucia (2015)
The aim of the final thesis is the feasibility survey of a novel business type in which I representing such enterprise where the different types of foods and beverages are not just consumed locally but they can be bought at the same time. One part of the room would operate as a catering unit, as a bistro and the other part would operate as a small shop, as delicacy. The planned business would not only provide new in the abovementioned. It would put more emphasis on supporting agriculturist, on introducing the local products and of course using the fresh, possibly regional products. In the first part of my thesis the strategic plan was detailed since the wording of the aims is one of the most important in case of starting enterprise. Then it follows the survey of the external and internal facts by using the models of SWOT, PESTEL and Porter five forces analysis. In this chapter the comprehensive list of the products, services can be found and the analysis of the target group, industry and competitors. Later, in the framework of the calculations of efficiency of investment, the budget-priced character of the investment is determined by the help of the IRR, the NPV, the index of dynamic internal rate of return period and the velocity of circulation. Certainly the marketing plan is the part of the thesis, as well in which the online marketing is emphasised which is essential in today’s digitised world. In addition the selection of product policy is important, too because the business wants to exercise a premium product distributing and retail and catering trade activity. The financial plan which contains the result plan, the balance plan, the liquidity plan and the cash flow plan is the essential part of the survey. Besides the detailed analysis is supplemented by costbenefit indexes such as resource -, and financial structure and the indexes of capital recovery. Finally the thesis is finished by the summary of the results and proposal. According to the abovementioned the planned business can be operated cost-effectively considering the present economic situation. The capital assets are recovered in the fourth year of the useful length of life and it will be able to produce profit for six years. The investment is refunded 2, 5 times within ten years. The net present value is much higher than zero which confirms the economic profitability of the investment. The abovementioned calculations are based on planned sales revenues which are established in the present economic situation. However the value of the calculations can be damaged by possible, non-probable negatively affected of the sector statement of the statue or an economic ruin of the whole country